2010
DOI: 10.1108/14626001011068743
|View full text |Cite
|
Sign up to set email alerts
|

Business support for farmers: an evaluation of the Farm Cornwall project

Abstract: The third set of questions concerns the economic role and entrepreneurial capability of the farmer in Cornwall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
0
30
0
2
Order By: Relevance
“…Taking all these difficulties into account, it is hardly surprising that many owner/managers of SMEs and micro-organisations prioritise lifestyle considerations over growth (Gray, 1997). Recent research in the farm sector McElwee and Annibal (2010) suggests that farmers are similarly weak in these skills, particularly business and management skills, and farmers in the UK are experiencing great difficulty in accessing appropriate labour.…”
Section: Lloréns-montes 2006) Within the Agricultural Sector This Ementioning
confidence: 99%
See 1 more Smart Citation
“…Taking all these difficulties into account, it is hardly surprising that many owner/managers of SMEs and micro-organisations prioritise lifestyle considerations over growth (Gray, 1997). Recent research in the farm sector McElwee and Annibal (2010) suggests that farmers are similarly weak in these skills, particularly business and management skills, and farmers in the UK are experiencing great difficulty in accessing appropriate labour.…”
Section: Lloréns-montes 2006) Within the Agricultural Sector This Ementioning
confidence: 99%
“…The paper concludes by opening a discussion as to how theories of entrepreneurship may impact on this situation. The paper itself is a development of a qualitative case study of farmers in the (McElwee and Annibal, 2010). These studies concluded that farmers in these regions of the UK are faced with a number of key barriers to their entrepreneurial capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the increasing distance in time and space between consumer and farmer entails that consumers are less familiar with agricultural activities and processes (Lang 1999;Mcelwee and Annibal 2010). Consequently, consumers have to rely on farmers in many matters of agriculture because they lack the expertise and time to control all activities in the agro-food sector (Brom 2000;Meijboom 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in the farm sector in the UK Annibal, 2010, andVik and suggests that farmers are similarly weak in these skills, particularly business and management skills, and experience great difficulty in accessing and recruiting appropriate labour.…”
Section: Barriers To the Rural Enterprisementioning
confidence: 99%
“…Previous studies develop a descriptive taxonomy of what constitutes rural enterprise (see McElwee and Robson, 2005;McElwee and Annibal, 2010;. This chapter will review some of the important literature and develop extant typologies into a more robust conceptual model which outlines two ways of differentiating between an 'urban' and a 'rural' business.…”
Section: Introductionmentioning
confidence: 99%